Multifunctions of CRIF1 in cancers and mitochondrial dysfunction - Jiang, Yangzhou; Xiang, Yang; Lin, Chuanchuan; Zhang, Weiwei; Yang, Zhenxing; Xiang, Lixin; Xiao, Yanni; Chen, Li; Ran, Qian; Li, Zhongjun (Frontiers in Oncology, 2022)
Sustaining proliferative signaling and enabling replicative immortality are two important hallmarks of cancer. The complex of cyclin-dependent kinase (CDK) and its Cyclin plays a decisive role in the transformation of the cell cycle, and is also critical in the initiation and progression of cancer. CRIF1, a multifunctional factor, plays a pivotal role in a series of cell biological progresses such as cell cycle, cell proliferation and energy metabolism. CRIF1 is best known as a negative regulator of cell cycle, on account of directly binding to Gadd45 family proteins or CDK2. In addition, CRIF1 acts as a regulator of several transcription factors such as Nur77 and STAT3, and partly determines the proliferation of cancer cells. Many studies showed that the expression of CRIF1 is significantly altered in cancers and potentially regarded as a tumor suppressor. This suggests that targeting CRIF1 would enhance the selectivity and sensitivity of cancer treatment. Moreover, CRIF1 might be an indispensable part of mitoribosome and is involved in the regulation of OXPHOS capacity. Further, CRIF1 is thought to be a novel target for underlying mechanism of diseases with mitochondrial dysfunctions. In summary, this review would conclude the latest aspects of studies about CRIF1 in cancers and mitochondria related diseases, shed new light on targeted therapy, and provide a more comprehensive holistic view.